Multi-service network load management infrastructure - Filonenko, A. M.; Zhmutsky, I.; Rakityansky, M. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The Report considers the possibility of step-by-step creation of multi-service networks. From the parallel coexistence of NGN with existing networks to their absorption by the first.
Keywords: information technology; access networks; multiservice network infrastructure; Softswitch